Efektivitas Strategi Inquiry Dalam Meningkatkan Hasil Belajar Mahasiswa Mata Kuliah Sistem Informasi Perbankan - Nurbaiti Sirait (Universitas Islam Negeri Sumatera Utara, 2018)
This study aims to know the student learning outcomes by using brainstorming method, conventional methods and knowing the difference between both of the 2 learning methods in the course of banking information systems . The objects are the students of semester V of Islamic Economics Program about 62 students with random sampling. In this research, the researchers succeeded in obtaining the values for the normality test in the experimental class on the pre-test obtained Lstat = 0.122, while in the post-test Lstat= 0,093 and for the control class on the pre-test Lstat = 0.129, while in the post-test 0.102, then the Ltabel = 0.159 with the two classes having the same number of students, means the data is normally distributed. For homogeneity test the value of pre-test obtained Fstat = 1.61 and the value of post-test diperleh Fhitung = 1.17, while for Ftabel = 1.84, which means the two samples each homogeneous. As for the hypothesis test t obtained price t count = 2.389 and ttable = 2,000. Which means t-stat > t-table, that is 2,389 > 2,000 means there are differences in learning outcomes in banking information system courses that are taught by brainstorming and conventional methods.